Ética ambiental: uma abordagem pela teoria sistêmica da comunicação - Silva, Wagner Francisco da (2010)
This piece investigates the emergence of Environmental Ethics in environmental and psychosocial system using the method of the system. Its approach to the communicative dimension of ecological thinking and systemic. The research proposal has led to an analysis by the Environmental Ethics of metaphysics Peirceana (Ibri, 1992) the concepts of chance and continuity, finding support in the mechanism of action of empathy (Damásio, 1999 and 2004). We emphasize that our interest in this work is governed by ontological issues. Addressing some theories such as (the ontology of Mario Bunge Systemic and that of C. S. Peirce, the theory of Umwelt Jakob von Uexküll and caused a systemic theory of communication) to support the emergence of Environmental Ethics is the path chosen, as they have purpose is to investigate the nature of the systemic and complex reality of the human species. So these theories guide us to think about levels of knowledge, showing that kind of knowledge requires the Environmental Ethics. It was possible to see that the challenges posed by the object - Environmental Ethics - have significant implications on the role (and power) of the media in the implementation of such ethics